Protocol: low cost fast and efficient generation of molecular tools for small RNA analysis - Diego López-Márquez; Ángel Del-Espino; Eduardo R. Bejarano; Carmen R. Beuzón; Javier Ruiz-Albert (Plant Methods, 2020)
Abstract Background Small RNAs are sequence-dependent negative regulators of gene expression involved in many relevant plant processes such as development, genome stability, or stress response. Functional characterization of sRNAs in plants typically relies on the modification of the steady state levels of these molecules. State-of-the-art strategies to reduce plant sRNA levels include molecular tools such as Target Mimics (MIMs or TMs), Short Tandem Target Mimic (STTMs), or molecular SPONGES (SPs). Construction of these tools routinely involve many different molecular biology techniques, steps, and reagents rendering such processes expensive, time consuming, and difficult to implement, particularly high-throughput approaches. Results We have developed a vector and a cloning strategy that significantly reduces the number of steps required for the generation of MIMs against any given small RNA (sRNA). Our pGREEN-based binary expression vector (pGREEN-DLM100) contains the IPS1 gene from A. thaliana bisected by a ccdB cassette that is itself flanked by restriction sites for a type IIS endonuclease. Using a single digestion plus a sticky-end ligation step, the ccdB cassette that functions as a negative (counter) selection system is replaced by a pair of 28 nt self-annealing primers that provide specificity against the selected target miRNA/siRNA. The method considerably reduces the number of steps and the time required to generate the construct, minimizes the errors derived from long-range PCRs, bypasses bottlenecks derived from subcloning steps, and eliminates the need for any additional cloning technics and reagents, overall saving time and reagents. Conclusions Our streamlined system guarantees a low cost, fast and efficient cloning process that it can be easily implemented into high-throughput strategies, since the same digested plasmid can be used for any given sRNA. We believe this method represents a significant technical improvement on state-of-the-art methods to facilitate the characterization of functional aspects of sRNA biology.